A Literatur Review in Learning Organization - Eyo Itam Eyo; Denok Sunarsi; Herling Herling; Nurjaya Nurjaya; Azhar Affandi (International Journal of Educational Administration, Management, and Leadership, 2022)
The learning organization idea represents a shift in how organizations are developed and grow. Within the training and development literature, staff development and individual learning were emphasized. This review undertakes a critical review of the confused and confusing literature on the learning organization. Draws on both psychological and organizational perspectives and focuses on the distinction between organizational learning and the concept of the learning organization. The discussion is centered around the issues of learning organization and the nature of learning organization. The issues include the neglect of intra-organizational phenomena and a lack of clarity regarding the treatment of the organization, the nature of learning itself, the lack of an accepted theory of what constitutes a learning organization's culture and climate, the impact of organizational size, the role of teamwork within the learning organization concept, and the fundamental question of whether the learning organization is a variable or a root metaphor. This article looks at some of the problems with the learning organization literature and then asks whether the learning organization is a concept that is applicable to organizations. Much of the literature on organizations doesn't take into account the unique nature of organizations in terms of their membership and the people with influence within them. Collaborative learning allows employees to gain new knowledge, skills, and attitudes by working together. Finally, it concludes with a consideration of the issues involved in creating a learning organization.